IMPROVING THE EFFICIENCY OF URBAN TRANSPORT INFRASTRUCTURE BASED ON DIGITAL TECHNOLOGIES - S. N. Gagarina; N. N. Chausov; V. N. Levkina (Вестник университета, 2020)
The need to improve the efficiency of transport infrastructure, which is an important subsystem of urban services as a determinant of the quality of life of the city’s population, has been substantiated. The factors that determine the quality of the urban transport system, the features of urban transport have been highlighted. Transport infrastructure development in Russia has been analysed. It has been proved that in the conditions of the formation of the digital economy, artificial intelligence systems are an effective tool for decision-making. In the formation of intelligent systems for managing urban transport flows, the use of network models has been proposed, for which mathematical methods are necessary to obtain not only point, but also interval estimates of the model parameters, taking into account a priori uncertainty.